Transflective BPIII mode with no internal reflector. Issue 3 (19th February 2017) - Chen, Hui-Yu; Lu, Sheng-Feng; Wu, Pin-Hung; Wang, Ching-Sheng
ABSTRACT: A transflective device without reflector using room temperature blue phase III (BPIII) material is demonstrated in this study. In this device, the coupling of an induced birefringence and field-induced BP, relating the ordered orientation of the double-helix cylinders, causes the reflection and transmission. Compared with other reported transflective liquid crystal devices, the BPIII device shown here does not need any type of internal reflector. Well-matched voltage-dependent transmittance and reflectance curves can be obtained easily without considering the cell gap and incident wavelength. The total response time is less than 2 ms, which is also independent of the cell gap. The experimental results exhibit a simple way to get a transflective device with good ability based on the electro-optical properties of BPIII. GRAPHICAL ABSTRACT: